Getting into games - Breitenmoser, Kurt; Scoglio, Stephen; Video Education Australasia; Classroom Video (Firm) (Bendigo, Vic. : Video Education Australasia, 2009)
This Australian-made, curriculum fit program heras from gamers and game developers alike, taking a look behind the scenes at the gaming industry, the making of games, use of games for leisure and education, and taking a glimpse into the future of games
DVD format
Keywords: Electronic games industry; Video games industry; Computer games